2008
DOI: 10.1203/pdr.0b013e318186e609
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Developmental Model Organism for Pediatric Research

Abstract: Zebrafish has many advantages as a model of human pediatric research. Given the physical and ethical problems with performing experiments on human patients, biomedical research has focused on using model organisms to study biologic processes conserved between humans and lower vertebrates. The most common model organisms are small mammals, usually rats and mice. Although these models have significant advantages, they are also expensive to maintain, difficult to manipulate embryonically, and limited for large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 70 publications
0
110
0
1
Order By: Relevance
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Howe et al (2017) reported based on OMIM (Online Mendelian Inheritance in Man) tool that 82% of the genes involved in human disorders bear a strong resemblance with zebrafish. Zebrafish research is also guiding us to understanding the fundamental aspects of developmental stages (Van Slyke et al, 2014), embryogenesis (Veldman and Lin, 2008), fertility (Hoo et al, 2016) and treating human disease (Santoriello and Zon, 2012). Another attribute of zebrafish are their virtual transparency, which allows the observation of developmental processes using non-invasive imaging and tracking of protein/cell markers in biological and disease conditions (Spitsbergen, 2007, Blackburn et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…5 Genomic sequencing has shown extensive homology between zebrafish and other vertebrate species (including humans), and some aspects of brain patterning, structure and function are conserved. [6][7][8][9] They are being used as model systems for various human diseases. Current dogma states that size and/or surface area is the critical physicochemical property responsible for inducing nanoparticle toxicity.…”
mentioning
confidence: 99%